Tenascin‐C immobilizes infiltrating T lymphocytes through CXCL12 promoting breast cancer progression - Devadarssen Murdamoothoo; Zhen Sun; Alev Yilmaz; Gilles Riegel; Chérine Abou‐Faycal; Claire Deligne; Ines Velazquez‐Quesada; William Erne; Marine Nascimento; Matthias Mörgelin; Gérard Cremel; Nicodème Paul; et al. (EMBO Molecular Medicine)
Abstract Immune checkpoint therapy, where CD8 tumor infiltrating T lymphocytes (TIL) are reactivated, is a promising anti‐cancer treatment approach, yet with low response rates. The extracellular matrix, in particular tenascin‐C, may generate barriers for TIL. To investigate this possibility, we used a MMTV‐NeuNT and syngeneic mammary gland grafting model derived thereof with engineered tenascin‐C levels and observed accumulation of CD8 TIL in tenascin‐C‐rich stroma. Inhibition studies revealed that tenascin‐C induced CXCL12 through TLR4. By binding CXCL12, tenascin‐C retained CD8 TIL in the stroma. Blockade of CXCR4, the receptor of CXCL12, enhanced macrophage and CD8 TIL infiltration and reduced tumor growth and subsequent metastasis. Retention of CD8 TIL by tenascin‐C/CXCL12 was also observed in human breast cancer by tissue staining. Moreover, whereas high CD8 TIL numbers correlated with longer metastasis‐free survival, this was not the case when also tenascin‐C and CXCL12 levels were high. Altogether, these results may be useful for improving tumor immunity as diagnostic tool and to formulate a future “TIL‐matrix‐release‐and‐reactivate” strategy.